Regulation of O2 consumption by the PI3K and mTOR pathways contributes to tumor hypoxia - Kelly, Catherine J.; Hussien, Kamila; Fokas, Emmanouil; Kannan, Pavitra; Shipley, Rebecca J.; Ashton, Thomas M.; Stratford, Michael; Pearson, Natalie; Muschel, Ruth J. (Radiotherapy and oncology, 2014)
Inhibitors of the phosphatidylinositol 3-kinase (PI3K) and the mammalian target of rapamycin (mTOR) pathway are currently in clinical trials. In addition to antiproliferative and proapoptotic effects, these agents also diminish tumor hypoxia. Since hypoxia is a major cause of resistance to radiotherapy, we sought to understand how it is regulated by PI3K/mTOR inhibition. Whole cell, mitochondrial, coupled and uncoupled oxygen consumption were measured in cancer cells after inhibition of PI3K (Class I) and mTOR by pharmacological means or by RNAi. Mitochondrial composition was assessed by immunoblotting. Hypoxia was measured in spheroids, in tumor xenografts and predicted with mathematical modeling. Inhibition of PI3K and mTOR reduced oxygen consumption by cancer cell lines is predominantly due to reduction of mitochondrial respiration coupled to ATP production. Hypoxia in tumor spheroids was reduced, but returned after removal of the drug. Murine tumors had increased oxygenation even in the absence of average perfusion changes or tumor necrosis. Targeting the PI3K/mTOR pathway substantially reduces mitochondrial oxygen consumption thereby reducing tumor hypoxia. These alterations in tumor hypoxia should be considered in the design of clinical trials using PI3K/mTOR inhibitors, particularly in conjunction with radiotherapy.